Assessment of quality of life and physical and mental health in children and adolescents with coeliac disease compared to their healthy peers - Stojanović Bilјana; Medović Raša; Đonović Nela; Leković Zoran; Prokić Dragan; Radlović Vladimir; Jovanović Stevan; Vuletić Bilјana (Srpski Arhiv za Celokupno Lekarstvo, 2019)
Introduction/Objective. Strict gluten-free diet for life is the only treatment for patients with coeliac disease. Limited selection of food options can affect their quality of life and cause problems in acceptance by their peers. The aim was to examine the subjective quality of life experience in children and adolescents with coeliac disease and to obtain a comprehensive representation of physical and mental impairments and social functioning compared to their healthy peers. Methods. The study was conducted as a cross-sectional study. It included 116 respondents aged 5–18 years with coeliac disease and 116 healthy children of similar age and sex. A Serbian version of Pediatric Quality of Life Inventory (PedsQL) was used to measure the quality of life in children. Descriptive statistics were calculated to analyze all results, while t-test was used to compare them. Results. The mean value of total PedsQL score was lower in the coeliac disease patients (75.89 ± 20.35) than in the controls (86.35 ± 11.13). Additionally, the experimental group reported lower all PedsQL Scale scores than the control group in the domains of psychosocial, school, social, and emotional functioning. However, there was no statistically significant difference on the physical health scale. These results were the same in all age groups among both males and females. Conclusions. The disturbance of health-related quality of life in children and adolescents with coeliac disease is significant and the quality of life is lower if compared to their healthy peers.